PENGEMBANGAN BISKUIT MP-ASI DENGAN BAHAN DASAR KULIT PISANG AMBON (Musa Acuminata Colla) DAN PENAMBAHAN UBI JALAR MERAH (Ipomoea Batatas) UNTUK ANAK USIA 6-24 BULAN - Swamilaksita, Prita Dhyani; Noviyanti, Anugrah; Astuti, Rina Puji (Lembaga Penerbitan Unversitas Esa Unggul, 2019)
Banana skin contains nutrients that are high enough, especially in vitamins and minerals so that they can be used as raw material for food by processing it into flour. Banana skin flour can be used as a variety of processed foods. This study aims to develop snack alternatives for children aged 6-24 months in the form of MP-ASI biscuits with basic ingredients of Ambon banana peel and the addition of sweet potatoes in the hope that in addition to increasing nutritional value it can also increase the added value of the waste. This study uses experimental design carried out in March to November 2018. The flow of research includes (1) First Phase, namely the proposition research and (2) The second stage, namely the main research. Preliminary research includes preparation of tools and materials, then making basic ingredients namely banana peel flour and red sweet potato flour, as well as determining biscuit formulations. While the main research includes organoleptic tests (hedonic quality and acceptability), nutritional value tests (proximate test for macro nutrients and Î²-carotene test using HPLC), and tests of TPC (Total Plate Count) microbial contamination. The results showed that biscuits made from banana peel and red sweet potato met the SNI standard for MP-ASI so that it can be recommended for food for infants aged 6-24 months, but the temperature of storage, processing and packaging must be considered to be able to meet the requirements for food safety.Keywords: banana skin ambon, red sweet potato, mp-asi biscuits, baby food